Interparticle Distance Variation in Semiconductor Nanoplatelet Stacks. (27th February 2022) - Graf, Rebecca T.; Schlosser, Anja; Zámbó, Dániel; Schlenkrich, Jakob; Rusch, Pascal; Chatterjee, Atasi; Pfnür, Herbert; Bigall, Nadja C.
Abstract: In the large field of research on nanoplatelets (NPLs), their strong tendency to self‐assemble into ordered stacks and the resulting changes in their properties are of great interest. The assembly reveals new characteristics such as the charge carrier transport through the NPL assembly or altered optical properties. In particular, a reduced distance should enhance the charge carrier transport due to higher electronic coupling of neighboring NPLs, and therefore, is the focus of this work. To modify the inter‐particle distances, the straightforward method of ligand exchange is applied. Various CdSe and CdSe/CdX (hetero‐) NPLs serve as building blocks, which not only display different material combinations but also different types of heterostructures. The surface‐to‐surface distance between the stacked NPLs can be reduced to below 1 nm, thus, to less than the half compared to assemblies of pristine NPLs. Moreover, for certain NPLs stacking is only enabled by the ligand exchange. To characterize the ligand exchanges and to investigate the influences of the reduced distances, photo‐electrochemical measurements, fluorescence spectroscopy, energy dispersive X‐ray spectroscopy, nuclear magnetic resonance, and X‐ray photoelectron spectroscopy are performed. It is possible to show higher photocurrents for smaller distances, indicating enhanced charge transport ability within those stacks. Abstract : Nanoplatelets possess a large tendency to self‐assemble into ordered stacks. The influence of the assembly on the properties is thereby of great interest. This work focuses on the minimization of the inter‐particle distance via different ligand exchanges. Further, the influence of the smaller distances on the charge carrier transport within these assemblies are investigated through photo‐electrochemical measurements.